The Influence Of Corporate Social Responsibility And Social Media Use On Employee Green Behavior At PT Kreasi Karya Raya - Silviana Shalikhah (International Journal of Social, Economic, and Business, 2025)
PT Kreasi Karya Raya is a creative company that emphasizes the use of environmentally friendly materials, particularly recycled cardboard, in its products. Despite its commitment to sustainability through Corporate Social Responsibility programs and active social media use, the level of Employee Green Behavior adoption remains limited. This study aims to examine the influence of CSR and Social Media Usage on EGB within the company. A quantitative approach was employed using descriptive and causal research methods. Primary data were obtained from 42 employees through a structured questionnaire. The collected data were analyzed using multiple linear regression with SPSS software. The results show that SMU has a positive and significant effect on EGB, indicating that digital platforms play a critical role in promoting sustainable practices among employees by facilitating information sharing, interaction, and the formation of eco-conscious communities. Conversely, CSR was found to have a positive but statistically insignificant influence on EGB, suggesting that current CSR initiatives may not sufficiently engage employees or align with their environmental motivations. These findings imply that while CSR remains an important framework, internal sustainability communication strategies via social media can be more effective in fostering green behavior in the workplace. To strengthen EGB, companies should prioritize participatory communication models, enhance employee involvement in CSR, and continuously evaluate the relevance and impact of their sustainability initiatives.